Effect of Insitu Formed TiB2 Particles on Tribological Behaviour of Al-Si/Mg2Si Hybrid Composites - Yadav A.K.; Gautam G.; Mohan S. (My University, 2025)
This work investigates the effect of insitu formed TiB2 particles on tribological behaviour of Al-Si/Mg2Si hybrid composites. For this purpose, different amount of TiB2 particles (0, 1, 3, 5 wt.%) have been generated through stir casting method using the halide salts K2TiF6 and KBF4. The tribology test has been performed on the pin on disc tribometer at ambient conditions with different applied load (10 N to 40 N) and sliding distance (1000 m to 3000 m) at a fixed sliding speed. The evolved worn surfaces are also analysed with the use of SEM with EDS and AFM to examine the wear mechanism. Results indicate that with an increasing TiB2 particle amount, wear rate of hybrid composite decreases while CoF increases. However, with the increase of applied load and sliding distance the wear of hybrid composite increases. Minimum wear and highest CoF is observed in the hybrid composite having 5 wt.% TiB2 particles in Al-Si/Mg2Si. The observed tribological results are also correlated with microstructure, mechanical properties, worn surfaces profile and debris analysis of the hybrid composites. These developed hybrid composites could be utilized on those places where less wear and high friction are required such as brake and clutch systems. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.